Professional Anxiety Status among the Departments of Physical Education and Sports Teaching and Physical Education and Sports Education for the Disabled - Burak Canpolat, Mehmet Ilkim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: This research is a study on the professional anxiety situation of prospective Physical Education Teachers in Turkey. Professional anxiety levels of Physical Education Teacher candidates studying in two departments were evaluated for different variables. Aim: This research aims to evaluate the Professional anxiety of the Physical Education and Sports Teaching Department and Physical Education and Sports Education Department for the Disabled students who are prospective Physical Teachers in Turkey. Methods: This research is quantitative and scanning pattern research. 340 prospective Physical Education Teachers studying at universities in Turkey were included in the study. Candidates consisted of students from the Department of Physical Education and Sports Education and the Department of Physical Education and Sports Education for the Disabled. The "Occupational Anxiety Scale for Prospective Teachers" prepared by Cabı and Yalçınalp (2013) was applied to the candidates. The data obtained after the scale applied were analyzed with SPSS IBM SPSS 22.0 Pockate Program. Results: According to the results obtained, the anxiety level of the Physical Education Teacher in the Department of Physical Education and Sports Education for the Disabled is generally higher. In addition, according to the variables of department, grade, and gender, the differences between the two departments were found to be significant in some sub-dimensions. Conclusion: It has been observed that there may be some reasons for the higher occupational anxiety scores of the students of the Physical Education and Sports Education Department for the Disabled, which is a department that has just graduated in Turkey, compared to the other department. It has been observed that the candidates who have anxiety about teaching in different sub-dimensions generally have anxiety about employment.